Distribution characteristics and prognostic value of TIM-1 in patients with lung adenocarcinoma - Wen, Junxu; Yun, Wenhua; Chen, Yu; Yin, Xiaoyan; Cui, Wenxing; Yu, Minghao; Meng, Xiangjiao (Frontiers in Immunology, 2025)
BackgroundT-cell immunoglobulin and mucin domain-containing protein 1 (TIM-1) has been identified as a promoter of tumor cell viability, migration, and invasion. However, the precise role and distribution characteristics of TIM-1 within the tumor microenvironment (TME) remain critical areas of investigation.MethodsIn this study, multiplex immunofluorescence (mIF) was performed on tissue slides from 126 patients with lung adenocarcinoma (LUAD) to investigate the distribution patterns of TIM-1 and the prognostic significance of three TIM-1 positive immune cell populations in both the primary tumor and tumor-draining lymph nodes (TDLN).ResultsCompared to the primary tumor, TIM-1+CD8+T cells and TIM-1+B cells exhibited significantly greater density in the TDLN (p<0.0001, p<0.0001 respectively). In the primary tumor, lower TIM-1+B cell density was associated with longer overall survival (OS) (mOS, 84 vs. 54 months; p<0.0001, HR=2.574) and disease-free survival (DFS) (mDFS, 53.0 vs. 23.1 months; p=0.018, HR=1.721). In the TDLN, lower TIM-1+B cell density was also correlated with longer OS (mOS, not reached vs. 64.7 months; p=0.0019, HR=2.3502) and DFS (mDFS, 68.5 vs. 28.9 months; p=0.016, HR=1.707). Higher TIM-1+B cell density in the TDLN was associated with a lower proportion of mature tertiary lymphoid structures (TLS) (p=0.0009, r=-0.3990) and increased density of TIM-1+B cells in the tumor was linked to reduced CD8+ T cell density (p=0.016, r=-0.2788).ConclusionsOur findings confirm the immunosuppressive role of TIM-1+B cells in LUAD and suggest that TIM-1+B cells exert immune suppression by inhibiting TLS maturation and CD8+ T cell density. These findings highlight TIM-1+ B cells as a potential therapeutic target.